GE_GERICHTE C/24460/2002 vom 19. Januar 2007 - GE Cour de justice (2007)
; DONATION ; NULLITÉ ; ERREUR ESSENTIELLE ; RÉVOCATION(EN GÉNÉRAL) ; DEMEURE DU DÉBITEUR | CO.23 CO.24 CO.107 CO.150 CO.239 CO.245.2 CO.246.1 CO.249.3